The Impact of Project Based Learning of Two Stay Two Stray Learning Model Toward the Learning Outcome Through Self-Regulated Learning as a Mediating Variable in Sekolah Penggerak - Qotrunnada, Alisa Beta; Andriansyah, Eka Hendi; Prakoso, Albrian Fiky; Dewi, Retno Mustika (AT-TA'LIM, 2023)
This research aims to analyze the impact of the Two Stay Two Stray (TSTS) model based on Project Based Learning (PjBL) towards student learning outcomes through self-regulated learning as a mediating variable in economics subjects in sekolah penggerak. This research is explanatory-quantitative research which aims to measure the cause-and-effect relationship between two or more phenomena. Data collection using questionnaire techniques with students' response questionnaires as research instruments. The results showed that: 1) The Two Stay Two Stray (TSTS) model based on Project Based Learning towards self-regulated learning proved to be significant and positive as shown by the path coefficient of 0.789 and p0.001; 2) The Two Stay Two Stray (TSTS) model based on Project Based Learning towards learning outcomes also proved to be significant as shown by the path coefficient of 0.154 and 0.013. This index is categorized as highly significant because the p value is less than equal to 0.01; and 3) Self-regulated learning proved to be a positive impact towards students' learning outcomes as shown by the path coefficient of 0.740 and p value of 0.014.